Impaired hydration status in acutely admitted older patients: prevalence and impact on mortality. (16th December 2020) - Sanson, Gianfranco; Marzinotto, Ilaria; De Matteis, Daniela; Boscutti, Giuliano; Barazzoni, Rocco; Zanetti, Michela
Abstract: Background: impaired hydration is common in the older people, however studies of its effects on outcome in the acute setting are limited. Objectives: to assess (i) the prevalence of impaired hydration, (ii) its relationship with laboratory markers of altered hydration and with (iii) short- and long-term mortality. Design: retrospective cohort study. Setting: University Hospital-Internal Medicine Department. Subjects: a total of 5, 113 older patients consecutively acutely admitted from October 2015 to July 2016. Methods: according to calculated serum osmolarity at admission hydration status was stratified in: low osmolarity (<275 mmol/L), euhydration (275–295 mmol/L), impending (296–300 mmol/L) and current dehydration (>300 mmol/L). Relationships with serum sodium, potassium, glucose, urea, estimated glomerular filtration rate (eGFR), haematocrit, urea/creatinine ratio (Urea/Cr) and urine specific gravity (USG) were determined. Charlson Comorbidity Index, Modified Early Warning Score, Glasgow Prognostic Score, Norton score and Nutritional Risk Screening-2002 were calculated. Results: current and impending dehydration, euhydration and low-osmolarity were detected in 51.7, 17.1, 28.5 and 2.7% of the patients, respectively. Osmolarity correlated with urea ( r = 0.846). Associations with serum sodium, creatinine, eGFR and urea/Cr were low but significant, being negligible that with USG and haematocrit. Serum sodium and urea increased in the transition from low- to high-osmolarity ( P < 0.001 in all pairwise comparisons). In multivariate modelling current dehydration, functional dependence, clinical instability and high nutritional risk were associated ( P < 0.001) with reduced short- and long-term survival. Conclusions: impaired hydration is common in older people acutely admitted to medical care and is associated with poor outcome. Early assessment of calculated serum osmolarity is mandatory to target dehydration and hypoosmolar disorders.